Application of the International Diabetes Federation and American Diabetes Association criteria in the assessment of metabolic control after bariatric surgery. Issue 1 (19th August 2013) - Miras, A. D.; Risstad, H.; Baqai, N.; Law, S.; Søvik, T. T.; Mala, T.; Olbers, T.; Kristinsson, J. A.; le Roux, C. W.
<x xml:space="preserve">Abstract</x> The International Diabetes Federation (IDF) and the American Diabetes Association (ADA) have introduced specific criteria to define the 'optimization' of the metabolic state and glycaemic 'remission' of type 2 diabetes mellitus (T2DM) after bariatric surgery, respectively. Our objective was to assess the percentage of patients achieving these criteria. Data were collected for body mass index, glycaemic markers, lipids, blood pressure, hypoglycaemia and medication usage from 396 morbidly obese T2DM patients who underwent bariatric surgery in two centres and followed up for 2 years. At year 1, 14% of patients achieved the IDF criteria and 38% the ADA criteria, whereas at 2 years 8 and 9% satisfied these criteria, respectively. A relatively low proportion of patients achieved optimization of the metabolic state and T2DM remission. These patients may potentially benefit from the combination of bariatric surgery and adjuvant medical therapy to achieve optimal metabolic outcomes.